Drying and storage of Piptadenia gonoacantha (Mart.) J.F.Macbr. seeds - J. M. Freire; T. B. Breier; Z. M. Moreira; L. F. D. de Moraes; J. R. C. Rouws (Brazilian Journal of Biology)
Abstract The objective was to evaluate the sensitivity of Piptadenia gonoacantha seeds to desiccation and storage conditions. The seeds were subjected to artificial drying in a forced air convection oven (39.7 °C ± 0.78 and 28.1% ± 1.90 RH) for different periods. After each drying period, evaluation methods were performed to determine the seeds water content and germination (germination test). The seeds were divided into two lots in the storage experiment: with previous drying (at 6.0% water content) and without previous drying (control, at 11% water content), and were stored for 36 months in a plastic bag in three conditions: refrigerator at 5 °C, freezer at -20 °C and natural condition (29 °C). The seeds were removed every three months and subjected to water content measurement and germination tests. The reduction of the initial water content of the seeds from 14% to 6% upon artificial drying resulted in the loss of 1/3 of their viability, suggesting that the seeds are sensitive to desiccation. The best practice to store seeds of P. gonoacantha found in this study was without previous drying, into the freezer. The seeds lost only 14% of their germination after 36 months under these conditions.